Determinants of Foreign Direct Investment in SAARC Countries: An Investigation Using Panel VAR Model - Pradhan, Rudra P. (Information Management and Business Review, 2011)
Foreign direct investment (FDI) is considered to be a policy variable to enhance economic growth in the economy. So identifying the determinants of FDI is very challenging among the policymakers. The paper examines the determinants of foreign direct investment in seven SAARC countries over the period 1980-2010. Using panel VAR model, the paper finds that foreign direct investment are largely influenced by economic growth, exchange rate, inflation, labor population, trade balance, current account balance and long term debt outstanding. The impact of economic growth and exchange rate are bidirectional, while the other factors are unidirectional on FDI inflows.